Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, Hassan; Bernlöhr, Konrad; Glawion, Dorit; Hinton, James Anthony; Hofmann, Werner; Jankowsky, Felix; King, Johannes; Marx, Ramin; Mohamed, Mahmoud; Rieger, Frank M.; Schwemmer, Stephanie; Völk, Heinrich J.; et al. (Nature astronomy, 2020)
An angular extension at gamma-ray energies of 52 arcseconds is detected for the Crab nebula, revealing the emission region of the highest-energy gamma rays; simulations of the electromagnetic emission provide a non-trivial test of our understanding of particle acceleration in the Crab nebula.